Change and Maintaining Change (Nebraska Symposium on Motivation, 2018)
This unique multidisciplinary volume examines the dynamics of behavioral change and its maintenance, from the individual to the wider domains of public policy. Coverage traces how change may be achieved, sustained, or derailed, as well as underlying neurobiological, behavioral, and social processes that fuel unhealthy and risky behaviors. Contributors offer a wide range of prevention and intervention strategies for supporting positive health habits from improved food choices to abstinence to compliance with treatment. These mechanisms are then transferred to the societal level in studies of evolving public perception of salient issues such as climate change, gender disparities, and drug policy. Included among the topics: Motivating change in addiction via modulation of the dark side. Changing drug use and other health-related behavior in vulnerable populations. Change and maintaining change in school cafeterias. Understanding social structural barriers and facilitators to behavioral change. Strategic communication research to illuminate and promote public engagement with climate change. A provocative rendering of motivation in its macro and micro dimensions, Change and Maintaining Change will interest researchers, practitioners, and clinicians interested in diverse areas such as smoking and other addictions, improvement and relapse in therapy, development and treatment of anxiety disorders, and social cognition and decision-making.